Internalization of Religious Educational Values in Developing Students’ Interpersonal Intelligence - Anwar, Anwar (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose of the study is to reveal how the internalization of religious education values contributes to the development of students’ interpersonal intelligence. Methodology: This study employs a literature research approach. The search for scientific articles related to ‘internalization of religious education’ was conducted through Google, ScienceDirect, Emerald, and Tandfonline. Main findings: Islamic religious education contributes to the growth of students’ interpersonal intelligence through the internalization of religious values, educational experiences, the selection of role models, self-reflection, and a commitment to continuous learning. Applications of this study: Islamic religious education should prioritize moral values, prosocial behavior, empathy, cooperation, forgiveness, interfaith dialogue, togetherness, experiential learning, critical thinking, self-reflection, and respect for diversity novelty/originality of this study: This study introduces a novel approach by integrating Islamic education with the development of interpersonal intelligence.